2021
DOI: 10.1590/1519-6984.224774
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of biological control for fall armyworm resistant to the protein Cry1F

Abstract: Understanding the ecological and toxicological relationship between genetically modified cultivars (GM) and biological control agents is of great importance for discussions related to the compatability of GM cultivars and integrated management strategies for pest resistance. The present study evaluated the search behavior and predatory capacity of Orius insidiosus (Say) (Hemiptera: Anthocoridae) and Doru luteipes (Scudder) (Dermaptera: Forficulidae) on eggs and caterpillars of Spodoptera frugiperda (J. E. Smit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…The results suggest that sublethal effects of Bt could synergize with the direct mortality caused by Bt proteins in the presence of certain natural enemies, enhancing biological control. Similar positive or neutral indirect interactions between Bt and natural enemies have been found in other studies [ 56 , 57 , 72 , 73 ]. This would also help explain other reports of synergistic interactions between Bt and natural enemies such as the delayed development of resistance to Bt toxins [ 74 ].…”
Section: Discussionsupporting
confidence: 89%
“…The results suggest that sublethal effects of Bt could synergize with the direct mortality caused by Bt proteins in the presence of certain natural enemies, enhancing biological control. Similar positive or neutral indirect interactions between Bt and natural enemies have been found in other studies [ 56 , 57 , 72 , 73 ]. This would also help explain other reports of synergistic interactions between Bt and natural enemies such as the delayed development of resistance to Bt toxins [ 74 ].…”
Section: Discussionsupporting
confidence: 89%
“…They found that combining the fungal pathogen and the lure significantly reduced fall armyworm damage to maize plants. However, it is important to note that the actual effectiveness of this biological control agent can vary depending on various factors 30 , including climatic conditions 31 , application methods 32 and population dynamics of the pest 33 .…”
Section: Discussionmentioning
confidence: 99%
“…This finding highlights the need for a diversified diet and reinforces the omnivorous habit of D. luteipes. From this perspective, the known voracity of D. luteipes (Souza et al, 2021;Romero-Sueldo and Virla, 2017), suggests that this predator has a great potential to reduce prey and fungal pathogens in maize fields. Also, in the maize reproductive stage, the pollen functions as an essential factor attracting and maintaining D. luteipes in the maize cultures.…”
Section: Discussionmentioning
confidence: 99%